The impacts of omnichannel retailing properties on customer experience and brand loyalty: A study in the banking sector - Quynh Tran Xuan; Hanh T.H. Truong; Tri Vo Quang (Cogent Business & Management, 2023)
Omnichannel retailing is regarded as an emerging trend in banking. The purpose of this study is to analyze the potential effects of omnichannel retailing properties on customer experience and brand loyalty; it further explores the moderating role of transaction channels. Its centrality has been focused on omnichannel retailing cues comprising integration quality, perceived fluency, and assurance quality; customer experience is analyzed through hedonic and utilitarian values. This study uses the non-probabilistic sampling technique with approximately 1547 respondents via the self-administered questionnaires. The findings indicate that perceived fluency and assurance quality are proved as the critical components of hedonic and utilitarian experiences. It has been found that increasing integration quality leads to a more positive perception of fluency and enhances omnichannel experience quality by switching various channels. This study validates the importance of hedonic and utilitarian experiences which significantly contribute to constituting brand loyalty between clients and banks in omnichannel retailing. The importance of various channels was affirmed as a significant moderator when indicating the effect of perceived fluency on customer experience via physical channels is stronger than digital channels. Applications and limitations are further discussed.
Keywords: 650; customer experience; integration quality; omnichannel retailing; perceived assurance; perceived fluency